LQ45 Companies: Dividend Policy To The Value Of Companies With Cash Holding As A Moderation Variable - Anny Widiasmara; Mayang Resqita Ayu Nadya (Profesional Muda Cendekia Publishing, 2022)
The rapid development of the business world at this time, which can be seen from the emergence of various competing companies with their respective advantages makes each company must continue to make changes and updates. This makes the competition in the business world continue to move and experience the dynamics of change very quickly. Each company will continue to compete to increase and maximize its profits and profits. The purpose of this study is to determine the influence of dividend policy, cash holding on company value and the influence of dividend policy on the value of companies moderated by cash holdings in LQ45 companies on the Indonesian stock exchange in 2012 - 2019. The data used in this study is secondary data from the Indonesia Stock Exchange (IDX). Sampling techniques using purposive sampling methods so that 22 companies were obtained. This research data analysis technique is multiple linear regression and Moderetted regression analysis test, data processed using IBM SPSS Statistics. The results of this study showed that dividend policies had a significant effect on the value of the company, and cash holding had no effect on the value of the company, and cash holding did not moderate the dividend policy on the value of the company.